Peran Duta Remaja Sadar Anemia dan pemberdayaan Teman Sebaya (Peer group Sharing) dalam Peningkatan Kadar Hb Remaja Putri - Yuniarti, Yuniarti; zakiah, zakiah; Maslani, Noorhayati; Farhat, Yasir (UPPM Poltekkes Kemenkes Banjarmasin, 2022)
Teenager girls one of vulnerable group to suffer anemia. The prevalence of anemia in South Kalimantan was still igh (17.81%). The Banjarbaru Health Departemen has carried out various efforts such as giving blood-added tablets (TTD) and checking for Haemoglobin (Hb) for teenager girls. This Activity aims to increase peer empowerment, increase understanding, knowledge and awareness of the teenager girls about anemia, body image, menstrual patterns, nutritional supplements and nutritional needs of teenager girls and healthy food. The target of this community sevice divided into the Sadar Anemia Youth Ambassadors was teenager girls from 5 (five) Senior High School, each school 2 students totaling 10 students., and target peer sharing group totaling 105 teenager girls. Implementation of this community service activity consists of several stages: stage Preparation, Stage Implementation: selection of the Sadar Anemia Youth Ambassadors, providing materials, and Implement peer group sharing. Results Implementation of Sadar Anemian Youth Ambassador was attended by 10 participants, hemoglobin test implemented on 131 teenager girls and found 32 teenager girls (24.4%) with anemia, Peer group sharing activity given Theory about anemia in teenager girls, body image, menstrual pattern, nutritional supplements, nutritional needs of teenager girls and last pre-posttest. At the pretest, level knowledge participants an average of 60% or level knowledge medium. Whereas on the posttest, knowledge level increase with an average of 87%, or level knowledge good, so could concluded knowledge teenager daughter increase by 27%.